2014
DOI: 10.1002/prep.201300017
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Sensitivity of Energetic Compounds with a New Computer Code

Abstract: Simple and reliable approaches have been recently introduced to predict impact, electrostatic and shock sensitivities of energetic compounds [1][2][3][4][5][11][12][13][14][15][16][17][18][19][20][21]. Impact SensitivityThe impact sensitivity test involves subjecting a sample to the impact of the standard mass falling from different Abstract: Impact, electrostatic, and shock sensitivities of energetic compounds are three important parameters for the assessment of hazardous energetic materials. A novel easy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
(48 reference statements)
0
14
1
Order By: Relevance
“…Due to existence of a large number of experimental data of impact sensitivity for nitramines, different approaches have been developed to predict their impact sensitivity, e.g. by structural moieties . The following correlation provides a simple method for prediction of impact sensitivity of nitramines as Equation (1):[9a] E IS (J)=0.245× 10 0.584+61.62(a/Mw)+21.53(b/Mw)+27.96(c/Mw)+84.47( F + /Mw)147.1( F /Mw) where E IS and Mw (in g · mol –1 ) are impact sensitivity based on drop‐weight impact sensitivity and molecular weight of a desired nitramine compound, respectively; a, b, c , and d are the number of carbon, hydrogen, nitrogen, and oxygen atoms, respectively; the value of F – is 0.5 for all kind of nitramines except those nitramines containing the group =C–N–NO 2 , for which F + = 0.7.…”
Section: Initial Knowledgementioning
confidence: 99%
“…Due to existence of a large number of experimental data of impact sensitivity for nitramines, different approaches have been developed to predict their impact sensitivity, e.g. by structural moieties . The following correlation provides a simple method for prediction of impact sensitivity of nitramines as Equation (1):[9a] E IS (J)=0.245× 10 0.584+61.62(a/Mw)+21.53(b/Mw)+27.96(c/Mw)+84.47( F + /Mw)147.1( F /Mw) where E IS and Mw (in g · mol –1 ) are impact sensitivity based on drop‐weight impact sensitivity and molecular weight of a desired nitramine compound, respectively; a, b, c , and d are the number of carbon, hydrogen, nitrogen, and oxygen atoms, respectively; the value of F – is 0.5 for all kind of nitramines except those nitramines containing the group =C–N–NO 2 , for which F + = 0.7.…”
Section: Initial Knowledgementioning
confidence: 99%
“…The elemental compositions of different classes of energetic compounds are important parameters for assessment of their impact sensitivities [5][6][7][8][9][10][17][18][19][20]. For ionic liquids, it has been found that the elemental composition and the contributions of some cations or anions are important for the assessment of some properties such as density [21,22].…”
Section: Development Of the New Modelsmentioning
confidence: 99%
“…This parameter is measured by the height from which there is a 50% probability of causing an explosion. Even though there are the uncertainties associated with the impact sensitivity test, different methods have been developed for the prediction of the impact sensitivity of different classes of neutral energetic compounds, and these have been reviewed elsewhere [1,[5][6][7][8][9][10][11]. Since the impact sensitivity of an energetic material depends on the particle size distribution, morphology and the basic molecular structure, the results are often not reproducible [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Using the group additivity approach, Traver fitted the group volumes of NO 2 , OH, CH 3 , NH 3 , CO 2 H, and ONO 2 to solve the molecular volumes based on 25 explosives and 163 similar compounds containing those groups [19]. Keshavarz et al used the similar method to fit more general group volumes for estimation of the density of nitroaromatic explosives on the basis of larger nitroaromatic energetic compounds database [20][21][22]. However, the method is not suitable to N 4 (T d ) since it is lack of functional groups.…”
Section: Introductionmentioning
confidence: 99%